Effects of thermal diffusion and viscous dissipation on unsteady MHD free convection flow past a vertical porous plate under oscillatory suction velocity with heat sink - Prabhakar Reddy, Bijjula (Zielona Góra: Uniwersytet Zielonogórski)
The thermal diffusion and viscous dissipation effects on an unsteady MHD free convection heat and mass transfer flow of an incompressible, electrically conducting, fluid past an infinite vertical porous plate embedded in a porous medium of time dependent permeability under oscillatory suction velocity in the presence of a heat absorbing sink have been studied. It is considered that the influence of a uniform magnetic field acts normal to the flow and the permeability of the porous medium fluctuates with time.
Keywords: MHD; vertical plate; oscillatory suction velocity; heat sink; Galerkin FEM